Remitting infections due to community-acquired Panton-Valentine leukocidin-producing Staphylococcus aureus in the Milan area - Sara G. Rimoldi; Cristina Pagani; Erika Longhi; Valentina D. Cristo; Annamaria D. Gregorio; Alessandro Mancon; Pietro Zerbi; Cristina Gervasoni; Maria R. Gismondo; Agostino Riva (Elsevier, 2018)
One of the most important Staphylococcus aureus virulence factors is Panton-Valentine leukocidin (PVL). We describe an outbreak of recurrent cutaneous PVL infections in different members of three family clusters. Molecular investigations were performed to confirm the presence of the mecA and PVL genes and to assign the SCCmec type, sequence type (ST) and clonal relatedness. A strain of PVL-producing methicillin-resistant S. aureus (MRSA) was responsible for infection in two related families (A and B), and a third family (C) was infected with PVL-producing methicillin-sensitive S. aureus (MSSA). Molecular investigations revealed the same clone of community-acquired (CA)-MRSA, PVL positive ST8, and SCCmec IV in families A and B and CA-MSSA PVL positive ST15 in family C. S. aureus PVL may give rise to recurrent uncontrolled infections that are difficult to eradicate, and close family contacts are at high risk for transmission. Keywords: Panton-Valentine leukocidin, Community-acquired methicillin-resistant Staphylococcus aureus